Adipokinetic hormone regulates cytochrome P450-mediated imidacloprid resistance in the brown planthopper, Nilaparvata lugens. (November 2020) - Tang, Bingjie; Cheng, Yibei; Li, Yimin; Li, Wenru; Ma, Ying; Zhou, Qiang; Lu, Kai
Abstract: Insect resistance to chemical insecticide is a global problem that presents an ongoing threat to sustainable agriculture. Although the increased production of detoxification enzymes has been frequently implicated in resistance development, the mechanisms employed by insecticide-resistant insects for overexpression of these genes remain elusive. Here we report that neuropeptide adipokinetic hormone (AKH) negatively regulates the expression of CYP6ER1 and CYP6AY1, two important cytochrome P450 monooxygenases (P450s) that confer resistance to neonicotinoid imidacloprid in the brown planthopper (BPH). Imidacloprid exposure suppresses AKH synthesis in the susceptible BPH, and AKH is inhibited in the imidacloprid-resistant strain. RNA interference (RNAi) and AKH peptide injection revealed that imidacloprid exposure inhibits the AKH signaling cascade and then provokes reactive oxygen species (ROS) burst. These in turn activate the transcription factors cap 'n' collar isoform-C (CncC) and muscle aponeurosis fibromatosis (MafK). RNAi and ROS scavenger assays showed that ROS induces CYP6ER1 expression by activating CncC and MafK, while ROS mediates induction of CYP6AY1 through another unidentified pathway in the resistant BPH. Collectively, these results provide new insights into the regulation of insecticide resistance and implicate both the neuropeptide AKH-mediated ROS burst and transcription factors are involved in the overexpression of P450 detoxification genes in insecticide-resistant insects. Graphical abstract: Image 1 Highlights: The inhibition of AKH upon exposure to imidacloprid provokes ROS burst. ROS burst activates CncC and MafK, which then induces the expression of CYP6ER1. ROS induces the expression of CYP6AY1 through a CncC/MafK-independent pathway. CYP6AY1 and CYP6ER1 confer resistance to imidacloprid in the BPH.